Quantitative trait locus mapping and functional genomics of an organophosphate resistance trait in the western corn rootworm, Diabrotica virgifera virgifera. Issue 1 (14th November 2015) - Coates, B. S.; Alves, A. P.; Wang, H.; Zhou, X.; Nowatzki, T.; Chen, H.; Rangasamy, M.; Robertson, H. M.; Whitfield, C. W.; Walden, K. K.; Kachman, S. D.; French, B. W.; et al.
Abstract: The western corn rootworm, Diabrotica virgifera virgifera, is an insect pest of corn and population suppression with chemical insecticides is an important management tool. Traits conferring organophosphate insecticide resistance have increased in frequency amongst D. v. virgifera populations, resulting in the reduced efficacy in many corn‐growing regions of the USA. We used comparative functional genomic and quantitative trait locus (QTL) mapping approaches to investigate the genetic basis of D. v. virgifera resistance to the organophosphate methyl‐parathion. RNA from adult methyl‐parathion resistant and susceptible adults was hybridized to 8331 microarray probes. The results predicted that 11 transcripts were significantly up‐regulated in resistant phenotypes, with the most significant (fold increases ≥ 2.43) being anα ‐esterase‐like transcript. Differential expression was validated only for theα ‐esterase (ST020027A20C03), with 11‐ to 13‐fold greater expression in methyl‐parathion resistant adults ( P  < 0.05). Progeny with a segregating methyl‐parathion resistance trait were obtained from a reciprocal backcross design. QTL analyses of high‐throughput single nucleotide polymorphism genotype data predicted involvement of a single genome interval. These data suggest that a specific carboyxesterase may function in field‐evolved corn rootworm resistance to organophosphates, even though direct linkage between the QTL and this locus could not be established.